DETERMINAN KUALITAS LAPORAN KEUANGAN UKM INTEGRASI ASPEK TEKNOLOGI, TATA KELOLA DAN KAPABILITAS SDM: Teknologi Informasi, Umur Usaha, Kompetensi SDM, Pengendalian Intern, Kualitas Laporan Keuangan - Mukoffi, Ahmad; Himawan Wibisono, Sukarno; As'Adi; Junaidar Handayanto, Adrian; Marija (Jurnal Paradigma Ekonomika, 2026)
The aim of this study is to analyse the influence of the use of information technology, the age of the business, human resource (HR) competence, and internal control on the quality of financial reports of Small and Medium-sized Enterprises (SMEs) in Malang City. The research method used was explanatory quantitative analysis. The population for this study comprised 3,209 SMEs in Malang City, with a sample of 99 respondents selected using purposive sampling. The data were analysed using multiple linear regression via SPSS. The results indicate that, individually, the use of information technology (p=0.043), business age (p=0.010) and internal controls (p=0.008) have a positive and significant effect on the quality of financial statements. Meanwhile, HR competence (p=0.165) does not have a significant effect. Simultaneously, all four variables had a significant effect on the quality of financial statements, with a significance level of 0.002. The adjusted R-squared value of 0.161 indicates that 16.1 per cent of the variation in the quality of financial statements can be explained by the independent variables in this model, whilst the remainder is explained by other factors outside the scope of this study.